Measurement of radon (222Rn) in thermal water of Cerro Pacho, Coatepeque Caldera, El Salvador - Rodríguez, Ramiro (2014)
Radon (222Rn) concentrations and radio (226Ra) evaluation dissolved in thermal spring water are presented. The aim is to contribute to volcanic monitoring, adapting and validating analytical methodology. Sampling was discreet and monthly type, from June 2011 to March 2013. Radon levels vary from 0,48 ± 0,1 to 1,54 ± 0,13 Bq/L (average 1,24 Bq/L); radio concentrations were evaluated from January to December 2012, the values found do not show radio detection confidence level of 95% with respect to the detection limit (4,2 mBq/L). In November 2012 there was a reduction of radon possibly related to subduction anomalies with epicenter at 143 km from cerro Pacho, volcanic seismicity was also recorded 40 days before with increments of microearthquakes and volcano-tectonic activity. The study produced the first measurements of radon in thermal water, setting the baseline for evaluating the behavior of these radionuclides with seismic activity.